Memory's legion ebook The complete expanse story collection. - Corey, James S. A. (The Expanse., 2022)
From Leviathan Wakes to Leviathan Falls , James S. A. Corey's Hugo Award-winning Expanse series has redefined modern space opera. Now, available in print for the first time comes the complete collection of short fiction set in the Expanse universe, including both a brand-new novella set after the events of Leviathan Falls and author’s notes on each story. On Mars, a scientist experiments with a new engine that will one day become the drive that fuels humanity's journey into the stars.  On an asteroid station, a group of prisoners are oblivious to the catastrophe that awaits them.  On a future Earth beset by overpopulation, pollution, and poverty, a crime boss desperately seeks to find a way off planet. On an alien world, a human family struggles to establish a colony and make a new home. All these stories and more are featured in this unmissable collection of short fiction set in the hardscrabble world of The Expanse. Contents: The Expanse Short Fiction Drive The Butcher of Anderson Station The Churn Gods of Risk The Vital Abyss Strange Dogs Auberon The Sins of our Fathers —- For more from James S. A. Corey, check out: The Expanse Leviathan Wakes Caliban's War Abaddon's Gate Cibola Burn Nemesis Games Babylon's Ashes Persepolis Rising Tiamat's Wrath Leviathan Falls